Frontispiece: Magnetic Control of MOF Crystal Orientation and Alignment. Issue 62 (7th November 2017) - Cheng, Fei; Marshall, Ellis S.; Young, Adam J.; Robinson, Peter J.; Bouillard, Jean‐Sebastien G.; Adawi, Ali M.; Vermeulen, Nicolaas A.; Farha, Omar K.; Reithofer, Michael R.; Chin, Jia Min
Abstract : Lining up like soldiers – dynamic control over the orientation of free‐standing MOF crystals in different fluid matrices has been achieved through magnetic alignment. Magnetically aligned NU‐1000 crystals were shown to display an anisotropic optical response to linearly polarized excitation, underscoring the importance of controlling MOF crystal orientation. For more information, see the Communication by J. M. Chin et al. onpage 15578 ff.